Analysis of elastic properties of thin-walled structures designed by SADSF method - MARKIEWICZ, I. (Engineering Transactions, 2009)
The paper presents the results of analyses of elastic properties of thin-walled structures designed by means of the SADSF method, carried out in order to confirm its practical usefulness. The SADSF method makes it possible – without applying any iterative correction procedures – to effectively solve the problems of design of such structures. The method can be applied in cases when only boundary conditions are given. The obtained solutions are free of the structural errors which can significantly deteriorate load carrying ability of structures of this class.